Image Management Member of the House of Regional Representative of the Republic of Indonesia Riau Electoral District 2019: A Case Study of Intsiawati Ayus - Sami'an; Harmonis (JOELS: Journal of Election and Leadership, 2024)
This research discusses the Image Management of the elected Member of the Regional Representative Council Intsiawati Ayus in 2019 Riau electoral district, where building a good image in the community is an important thing for a politician to do, so that at the time of the election the public wants to vote for politicians who are running for legilative members. especially the competition between candidates is considered very significant which makes politicians have to make special strategies in the election process, Moreover, the competition between candidates is considered very significant which makes politicians have to make special strategies in the election process and the focus of this research is to understand the Political Public Relations (PR) Activities of Intsiawati Ayus' Image Management in the Election of Members of the Regional Representative Council of the Republic of Indonesia) Riau Electoral District in 2019 using qualitative methods reinforced by a literature study approach. Data collection techniques are carried out by interview where the information is determined by purposive sampling. The results obtained in this study found that there are interactions on social media that add to the positive image of Intsiawati Ayus in the community, because Intsiawati Ayus and the success team respond to the slightest interaction from the community, then advocacy in the agrarian sector carried out by Intsiawati Ayus also adds to the good image in the community, the attachment of the character's name through the organization is also an important part of Intsiawati Ayus' image, this name attachment is done through the Rumpun Melayu Bersatu Laskar Hulubalang Melayu Riau (RMB-LHMR) organization founded by Asman Yunus who is Intsiawati Ayus' father. The results of this study are expected to be used as a study material in the field of political PR, especially in the election of the Regional Representative Council of the Republic of Indonesia RI members in Indonesia.